ANALYSIS OF DEIXIS IN THE STORY SELECTED FROM CHRISTIAN BIBLE, GENESIS - Sisilia Viona Anugrah (PROJECT (Professional Journal of English Education), 2018)
Language is more than a sign as it can function as a tool for communication among humans. This means that  language  can  be  learned  by  the  humans.  One  of  the  fields  that  study  the  language  is  pragmatics. Pragmatics can be defined as the study of contextual meaning; therefore there should be a relationship between  language  and  the  context.  However,  this  relationship  can  be  recognized  through  deixis.  The purpose  of  this  paper  is  to  analyze  the  types  of  deixis  found  in  Chistian Bible, Genesis chapter 6, 7, 8, 9, 10.  This paper uses descriptive qualitative method, because it analyzes the types of deixis found in this novel. The  method of collecting the data is documentation. The deixis that mostly used in this bible is the person deixis with the frequency of 192 (39.91%). The following deixis is place deixis that appears 103 times (21.41%). The social deixis appears with the frequency of 83 (17.25%) while the time deixis appears with the frequency of 66 (13.72%). The final deixis that appears is discourse deixis with the frequency of 36 (7.69%). Keywords:      Deixis, Bible, Genesis